EFFECTIVENESS TEST OF THE CT-SCAN ROOM AT THE RADIOLOGY DEPARTMENT OF SITI RAHMAH PADANG HOSPITAL - Artitin, Cicillia; Putri, Riri Kurnia; Nisa, Chairun (PT. Hafasy Dwi Nawasena, 2026)
Radiation protection is a measure taken to reduce the harmful effects of radiation on health due to radiation exposure. The effectiveness of radiation protection in a room is an important factor in ensuring the safety of patients, healthcare workers, and the surrounding environment from unwanted radiation exposure. Field observations in the CT-Scan room are directly adjacent to other installations such as the NICU, chemodialysis, polyclinics, and patient waiting rooms. This study aims to evaluate the effectiveness of the walls, doors, and leaded glass of the CT-Scan room in blocking radiation according to national radiation safety standards. The study used an experimental quantitative method in the CT-Scan room of the Radiology Installation of RSI Siti Rahmah Padang on August 30, 2025 using a CT-Scan machine, a raysafe unforns X2 multimeter measuring instrument, a building meter measuring instrument and an air phantom. Measurement of the radiation dose rate at 12 different points, representing all components of the room structure, using exposure factors for the cranium, namely 130kv and 240 mAs. Measurements were made on the wall area leading to the surgical polyclinic, NICU room, control panel room, hemodialysis room, lead glass, and the main door, both from the inside and outside of the room. The effectiveness of radiation absorption was recorded in the range of 99.82% to 99.99%, with radiation passed less than 0.2% at all measurement points. The walls covered with 26 cm brick and 2 mm lead, as well as the doors and lead glass, were proven to meet and exceed the minimum effectiveness limit of 90% as stipulated by BAPETEN and the Indonesian Minister of Health Regulation. Thus, it can be concluded that the walls, doors, and lead glass of the CT-Scan room are effective in blocking radiation and have met radiation safety standards.